ISSUES OF INTRODUCING MODERN ARTIFICIAL INTELLIGENCE TECHNOLOGIES INTO THE ANTI-CORRUPTION EXPERT EXAMINATION OF NORMATIVE LEGAL ACTS (World Conference on Social Sciences, Law and Public Policy, 2026)
This article analyzes the issues of introducing modern artificial intelligence technologies into the process of conducting anti-corruption expert examination of normative legal acts and their drafts. The possibilities of artificial intelligence tools in identifying corruption-generating factors, increasing the efficiency and speed of expert examination procedures, and reducing errors associated with the human factor are highlighted. Furthermore, the legal, organizational, and technical aspects of implementing these technologies in practice are examined. The author proposes the introduction of an automated system for analyzing normative legal acts and substantiates its significance in preventing corruption and improving the quality of lawmaking.
Keywords: Normative legal acts, artificial intelligence, anti-corruption expert examination, strategy, corruption-generating factors, checklist.